STRENGTHENING THE EXISTENCE OF ISLAMIC RELIGION EDUCATION IN THE INDUSTRIAL REVOLUTION ERA 4.0 (Study of PAI FAI Curriculum Review of Muhammadiyah Gresik University) - Noor Amirudin (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Muhammadiyah Gresik, 2019)
This study provides an overview of the importance of massive reform in the Curriculum ofIslamic Religious Education at the Faculty of Islam, Muhammadiyah Gresik University. This reform isneeded so that the FAI UMG PAI curriculum can answer the challenges and demands of the times thatcontinue to change globally. Besides, this deafness also poured out the results of a solution to Islamicreligious education in the face of the Era of Industrial Revolution 4.0. As it is known, that the Era of theIndustrial Revolution 4.0 had a broad impact on all lines of life, including in the field of education,especially Islamic education. The era that gave birth to this disruption phenomenon demanded the worldof Islamic religious education to participate in adjusting. Graduates of Islamic education are now facedwith new challenges, demands, and needs that have never existed before. So it is necessary to updateand innovate the system, governance, curriculum, human resource competencies, facilities andinfrastructure, culture, work ethic, and others. Otherwise, Islamic religious education will beincreasingly left behind and outdated. Therefore, it is necessary to look for concrete steps for Islamicreligious education in order to be able to remain competitive in this disruption era. The solution step isto participate in discussing themselves.Keywords: Islamic religious education, industrial revolution 4.0, disruption